The Relation of Epistemology and Society in the View of Dr. Ali Shariati - Gholam Reza Jamshidiha; Hossein Ajdari Zadeh (Islām va ̒ulūm-i ijtimā̒ī)
The research aims to present the viewpoint of Shariati on the relation of epistemology and Society. Thus, the following generalities will be reviewed: introduction, problem exposition, questions, assumptions, background and theoretical framework based on the following five factors: depth of determination, degree of determination, level of determination, the dominant factor on determination and subject of determination. The research concludes with an evaluation of the reviewed subjects.